Material characterization of thin planar structures using full-field harmonic vibration response measured with stroboscopic holography. (15th May 2021) - Ebrahimian, Arash; Tang, Haimi; Furlong, Cosme; Cheng, Jeffrey Tao; Maftoon, Nima
Highlights: We propose a non-modal vibration-based method for material characterization. The method is developed for estimating the elasticity of thin planar structures. Our method works based on single frequency harmonic vibration data of whole domain. The method is robust to noise typical in holography measurements of soft tissue. Sensitivity of the method to uncertainties and measurement artefacts was studied. Abstract: We propose a novel material characterization method to estimate the Young's modulus of thin 2-D structures using non-modal noisy single frequency harmonic vibration data measured with holography. The method uses finite-difference discretization to apply the plate equation to all measured pixels inside the boundary of the vibrating structure and then treats the problem as a Bayesian optimization process to find the value of the Young's modulus by minimizing the Euclidian distance between the measured displacement field and repeatedly calculated displacement field using the plate equation. In order to assess the accuracy of the method, ground truth harmonic displacement magnitude fields of different plates were obtained using analytical solutions and the finite-element method and were used to estimate the Young's moduli. We applied Gaussian and non-Gaussian noise with different intensities to assess the robustness and accuracy of the proposed material characterization method in the presence of noise. We demonstrated that for multiple benchmarks for signal to noise ratio of down to 0 dB, our proposed method had errors of less than 5%. We also quantified the effects of uncertainties in the geometrical and material parameters as well as boundary conditions on the estimated Young's modulus. Furthermore, we studied the effects of the mesh size on the runtime and applied the method to experimental holography vibration measurement data of a copper plate. Graphical Abstract: Image, graphical abstract